KEPEMIMPINAN SEKOLAH DALAM KERANGKA MANAJEMEN BERBASIS SEKOLAH: ANALISIS MODEL, TANTANGAN, DAN INTEGRASI NILAI SPIRITUAL (STUDI PERSPEKTIF SEKOLAH BUDDHIS) - Lisniasari; Lamirin; Joko Santoso; Meiliana (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
The implementation of School-Based Management (SBM) positions principal leadership as a critical factor in improving educational quality. This article aims to analyze the strategic role, relevant models, and leadership challenges in strengthening SBM, with a focus on integrating spiritual values ​​in Buddhist schools. Using a qualitative literature study method with thematic analysis of current literature, the results show that principals must act as learning leaders, change agents, and resource managers. The success of SBM requires the synergy of transformational (vision-building), instructional (learning-focused), and distributive (collaborative) leadership models. In the Buddhist context, the spiritual values ​​of mettā (loving-kindness), karuṇā (compassion), upekkhā (equanimity), and paññā (wisdom) can be integrated to strengthen the ethical and relational foundations of all three models. Implementation challenges include leadership competency gaps, teacher resistance, limited resources, administrative burdens, and low community participation. Strategies to address these challenges require a holistic approach that goes beyond technical solutions to encompass sustainable capacity building, digitalization, the creation of a supportive school climate, and authentic community partnerships. This article concludes that strengthening MBS is essentially strengthening school leadership that is contextual, integrative, and based on values ​​to achieve holistic education.